Star Wars: um estudo sobre o universo da franquia cinematográfica - Ferraraz Junior, Claudio (Universidade Federal de São Carlos, 2012)
The major media conglomerates consolidated from the 1980s invest heavily on franchises captained by blockbusters movies and a wide range of products derived from them, in search of larger profits in the worldwide entertainment market. This study aims to analyze the marketing characteristics of franchises produced by major media conglomerates. In intend to do so, notes and appointments are made on the Star Wars film franchise, referred to as a kind of genesis for the franchise business model that the entertainment industry practices today. Star Wars created a paradigm in the production process of the Hollywood studios, combining filmic creativity with product marketing practices for disclosure and especially the development of strategic marketing licensing and merchandising of products that carry its brand. Through the analysis of the narrative structure of the Star Wars movies, creative tools used in the development of the story and its characters are identified showing possible paths for creating extensions and sequences that allow the expansion of several derived products across multiple platforms, building the media franchise.
Keywords: Cinema; Mídia; Merchandising; Blockbuster; Franquia; Star Wars; Cinema; Franchise; Media; Merchandising; Blockbuster; Star Wars; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA